Depression and Anxiety in Women Undergoing Therapeutic Abortion: The Effect of Spirituality - Kurt, Nuray; Çetin, Nurdilan Şener; Demirelli, Ayşegül (Hacettepe Üniversitesi, 2026)
[Abstract Not Available]
Keywords: Doğum ve Kadın Hastalıkları Hemşireliği